Lifetime Violence and Perinatal Sleep Quality: A Scoping Review - Agarwal, Nandini; Halim, Nafisa (Sleep Science, 2024)
Introduction In-utero experience of violence through maternal experience of intimate partner violence (IPV) is a risk factor for adverse pregnancy outcomes via ‘biological programming,’ whose effect can be mediated by sleep. We conducted a scoping review to synthesize the current evidence of the association between experiences of violence and sleep in women.Methods Between August and October 2023, we conducted a search in four databases (PubMed, APA PsycInfo, Embase, and Web of Science) for peer-reviewed articles, using 11 inclusion and exclusion criteria. Any study published in English in peer-reviewed journals that conducted original research on the association between exposure to violence (lifetime IPV, IPV during the previous year, during and 1 year after pregnancy, as well as adverse childhood experiences) and poor sleep outcomes (sleep disturbances, insomnia, poor sleep quality, and longer time to fall asleep) in the perinatal population were included.Results The synthesis of the 12 included studies revealed a positive association between exposure to violence and poor sleep, and between adverse childhood experiences and sleep disturbances or poor sleep during pregnancy. Moreover, IPV in the postpartum period was associated with poor sleep.Conclusion Most of the evidence synthesized comprises data from high-income countries, resulting in lack of cultural context. However, it is evident that the experience of violence throughout life is a risk for poor perinatal sleep quality. Thus, there is a growing need to study this association, especially in resource-limited settings, where data on sleep health is largely absent, inform pregnancy care and maternal and child health policies.
Keywords: intimate partner violence; ACE; lifetime violence; sleep; pregnant; postpartum